2007
DOI: 10.1007/s00125-007-0724-y
|View full text |Cite
|
Sign up to set email alerts
|

Betacellulin inhibits amylase and glucagon production and promotes beta cell differentiation in mouse embryonic pancreas

Abstract: Aims/hypothesis Betacellulin, a member of the epidermal growth factor family, is expressed in the pancreas and is thought to regulate differentiation of beta cells during development. The aim of the present study was to investigate the effects of exogenous betacellulin on the development of the mouse embryonic pancreas. Materials and methods We used an in vitro culture model system based on the isolation and culture of the dorsal embryonic pancreas from day 11.5 embryos. Cultures were treated for up to 10 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 42 publications
2
12
0
1
Order By: Relevance
“…And previous studies had shown that these PDX1+/NKX6-1+ pancreatic progenitors (PP2) could be further differentiated in vitro into some INS+ cells along with INS+/GCG+ or INS+/SST+ polyhormonal (PH) cells (Nostro et al, 2011; Rezania et al, 2012; Thowfeequ et al, 2007; Aguayo-Mazzucato et al, 2013; D’Amour et al, 2006; Hrvatin et al, 2014). We use the nomenclature PH (polyhormonal, Figure 1A) to refer to this cell population of in vitro differentiated hPSCs.…”
Section: Resultsmentioning
confidence: 99%
“…And previous studies had shown that these PDX1+/NKX6-1+ pancreatic progenitors (PP2) could be further differentiated in vitro into some INS+ cells along with INS+/GCG+ or INS+/SST+ polyhormonal (PH) cells (Nostro et al, 2011; Rezania et al, 2012; Thowfeequ et al, 2007; Aguayo-Mazzucato et al, 2013; D’Amour et al, 2006; Hrvatin et al, 2014). We use the nomenclature PH (polyhormonal, Figure 1A) to refer to this cell population of in vitro differentiated hPSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Transgenic mice overexpressing EGF under the insulin promoter showed an increased islet size and frequency of insulin positive cells in murine pancreatic ducts [46]. However, similar experiments on EGF treated pancreatic buds suggested that EGF might stimulate epithelial proliferation and thereby inhibit differentiation of pancreatic precursors to b-cells [47,48]. LIF is known to be expressed in pancreatic ducts [28], but evidence of its endogenous functions in pancreatic development are lacking.…”
Section: Discussionmentioning
confidence: 87%
“…For example, Sun et al showed that combined use of betacellulin and activin A was involved in the differentiation of bone marrow-derived mesenchymal stem cells from diabetic patients into IPCs [35]. On the other hand, Thowfeequ et al demonstrated that betacellulin inhibited amylase and glucagon production and promoted beta cell differentiation in mouse embryonic pancreas [74]. Using betacellulin and/or activin A, other studies have successfully differentiated stem cells of liver [40] and pancreatic [54] origins into IPCs.…”
Section: Methods and Extrinsic Factors Used In The Generation Of Imentioning
confidence: 99%